37 Prognostic role of the lung ultrasound in the acute coronary syndrome. (8th December 2021) - Tricarico, Lucia; Persichella, Paola; Mazzeo, Pietro; Leopizzi, Alessandra; Mallardi, Adriana; Magnesa, Michele; Fortunato, Martino; Croella, Francesca; Alfieri, Simona; Correale, Michele; Iacoviello, Massimo; Brunetti, Natale D
Abstract: Aim: Acute coronary syndromes (ACS) represent one of the major causes of mortality in our country. Lung ultrasound is an important diagnostic tool in the assessment of lung and pleural diseases; it is easy to perform and provides low-cost analysis and it is also easily learned with a few hours of training. To evaluate the usefulness of lung ultrasound in the early diagnosis of pulmonary congestion in patients admitted to ICU for ACS and to evaluate its possible prognostic role in the short and long term. Methods: Forty-three patients with ACS admitted in the ICU of Foggia were enrolled in the study between April 2020 and July 2020 (mean age 64.7 ± 12.7 years, male: 67.4%). Medical history, physical examination, ECG, blood analysis, chest X-ray, lung ultrasound and echocardiography were collected at the admission in ICU, after 24 h and at the dismission. All patients were re-evaluated, through a telephone follow-up 3 months after discharge. The primary endpoints were re-hospitalization at 30 days and the following MACEs: development of acute pulmonary oedema during hospitalization, cardiogenic shock, death and the need for oxygen therapy or the use of non-invasive ventilation. The secondary endpoints were out-of-hospital death from cardiac causes and re-hospitalization after 3 months. Results: The analysis of the ROC curves showed that pulmonary ultrasound performed on admission in the ICU predicted more than the thoracic physical examination [AUC 0.536 (0.367–0.699); P  = 0.111], chest radiograph (AUC 0.561 (0.391–0.721); P  = 0.109] and LVEF [AUC 0.525 (0.357–0.689); P  = 0.119], the risk of adverse cardiovascular events hospital, although not reaching the cut-off for statistical significance [AUC 0.661 (0.489–0.806); P  = 0.0895]. Among all in-hospital events, pulmonary ultrasound predicted higher sensitivity and specificity [AUC 0.665 (0.493–0.809); P  = 0.0927] than chest radiography [AUC 0.588 (0.417–0.745); P  = 0.113], clinical examination [AUC 0.550 (0.380–0.711); P  = 0.116] and LVEF [AUC 0.515 (0.348–0.680); P  = 0.125], the use of oxygen therapy and NIV during hospitalization stay. Conclusions: In patients with ACS, on admission lung ultrasound predicts the risk of in-hospital events, particularly the use of oxygen therapy or non-invasive mechanical ventilation more than physical examination, chest X-ray and LVEF estimated by echocardiography. It can be considered a complementary method to echocardiography in the evaluation of cardiac function, allowing to estimate the amount of extra-vascular lung water.